A New Species of Yeti Crab, Genus Kiwa (Decapoda: Anomura: Kiwaidae), from a Hydrothermal Vent on the Australian-Antarctic Ridge. Issue 2 (1st March 2016) - Lee, Sang-Hui; Lee, Won-Kyung; Won, Yong-Jin
Abstract: A new species of deep-sea yeti crab, Kiwa araonae, is described from a hydrothermal vent field, Mujin ("Misty Harbor"), at a depth of about 2000 m on the Australian-Antarctic Ridge (AAR), Southern Ocean. The Mujin vent field (62°11.79′S), in a large, unexplored gap in the Circum-Antarctic Ridge system, is the most southern record for a yeti crab to date. Kiwa araonae n. sp. is the fourth described species in the family Kiwaidae Macpherson, Jones and Segonzac, 2005, and the second known from the Southern Ocean. This new species differs morphologically from its three congeners by the having a nearly flat branchial region, relatively short rostrum, third sternite with parallel lateral margins, slender chela, straight fingers of the chela, and propodi of pereiopods 2-4 with three corneous spines on the flexor margins. The Bayesian phylogenetic tree and the genetic distance based on the mitochondrial 16S rRNA gene (408 bp) clearly indicate the distinctiveness of this species. The discovery of Kiwa araonae in the AAR suggests a possible biogeographic connection of the Southern Ocean vent faunas. The presence of a new hydrothermal vent field with endemic species in the AAR provides additional information on the global biogeography of deep-sea vent faunas.